Clostridium-difficile-assoziierte Infektionen im Kindes- und Jugendalter = Clostridium difficile-associated diseases in childhood and adolescence - Weichert, Stefan; Schroten, Horst (Monatsschrift Kinderheilkunde, 2015)
Background: In recent years there has been an increase in Clostridium difficile-associated diseases in childhood and adolecence. Aim: This article gives an overview of the incidence, morbidity and clinical characteristics of C.-difficile-associated diseases in childhood and adolescence as well as diagnostic algorithms and therapy recommendations. Material and methods: Analysis, discussion and summary of data from original studies, review articles as well as expert opinion are presented. Results: Despite an increase in C.-difficile-associated diseases in infants and children the mortality rates remained unaffected. The most relevant risk factor for developing disease is previous antibiotic exposure but specific underlying diseases as well as comorbidities also put children at increased risk. Infants < 1 year of age show high rates of colonization. In older symptomatic children C.-difficile-associated diseases are diagnosed using multi-step diagnostic algorithms. In children without underlying diseases or risk factors, the disease is often self-limiting after antibiotics have been withdrawn. For more severe or complicated cases additional treatment regimens exist. Specific hygiene measures help to lower the transmission of C. difficile, and establishing antibiotic stewardship programs can decrease the incidence rate of C.-difficile-associated diseases. Conclusion: Knowledge of the characteristics of C.-difficile-associated diseases in childhood and adolescence leads to a rational diagnostic and therapeutic approach. Furthermore, specific hygiene measures and antibiotic stewardship programs can significantly reduce the burden of C.-difficile-associated diseases.